An Implementation of TRIZ in Innovative Product Development: An Oil Cap for Propeller Shaft - Onur Şen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In today's competitive and rapidly developing market, the importance of innovative products is increasing. Innovative products are needed to maintain growth and competitiveness. For this purpose, companies study on innovative applications and try new methods in product development processes. In this context, this study focuses on integrating the TRIZ tool into the product development process and producing creative solutions to the problems encountered during the design and development phase. And the benefit of TRIZ is discussed by conducting a case study involving the development of an innovative product. In the case study, the development process of the oil cap, which is located on the propeller shaft used to transmit torque and rotation in motor vehicles and whose main function is to provide sealing between the external environment and the internal volume of the propeller shaft, is discussed. The reason why the oil cap was chosen as a case study was the difficulty encountered in the design process, as the oil cap was expected to both provide sealing and allow air flow in the area where it was positioned. TRIZ methodology was successfully implemented to development of the oil cap. As a result of the study, an innovative product was developed, and validated by implementing tests. Thus, TRIZ's contribution to innovative product development was objectively demonstrated with a case study in which a commercialized product was developed. Besides, a practical guide based on real study, which designers could apply in innovative product development, was presented by this study.